Engineering Escherichia coli to Utilize Erythritol as Sole Carbon Source - Fang Ba; Xiangyang Ji; Shuhui Huang; Yufei Zhang; Wan‐Qiu Liu; Yifan Liu; Shengjie Ling; Jian Li (Advanced Science)
Abstract Erythritol, one of the natural sugar alcohols, is widely used as a sugar substitute sweetener in food industries. Humans themselves are not able to catabolize erythritol and their gut microbes lack related catabolic pathways either to metabolize erythritol. Here, Escherichia coli (E. coli) is engineered to utilize erythritol as sole carbon source aiming for defined applications. First, the erythritol metabolic gene cluster is isolated and the erythritol‐binding transcriptional repressor and its DNA‐binding site are experimentally characterized. Transcriptome analysis suggests that carbohydrate metabolism‐related genes in the engineered E. coli are overall upregulated. In particular, the enzymes of transaldolase (talA and talB) and transketolase (tktA and tktB) are notably overexpressed (e.g., the expression of tktB is improved by nearly sixfold). By overexpression of the four genes, cell growth can be increased as high as three times compared to the cell cultivation without overexpression. Finally, engineered E. coli strains can be used as a living detector to distinguish erythritol‐containing soda soft drinks and can grow in the simulated intestinal fluid supplemented with erythritol. This work is expected to inspire the engineering of more hosts to respond and utilize erythritol for broad applications in metabolic engineering, synthetic biology, and biomedical engineering.